2008
DOI: 10.3892/or.19.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of SOCS-3 mRNA in breast cancer with lymph node metastasis

Abstract: Signal transducers and activators of transcription (STATs) play a pleomorphic role in signal transduction, similarly to an oncogene. Suppressors of cytokine signaling (SOCS) inhibit STAT pathways. In breast cancer, little is known about the correlation among STATs, SOCS, and clinicopathological/biological features. Therefore, we investigated p-STAT3 (activated form of STAT3) and SOCS-1/3 expression, and clarified their correlation. Immunohistochemical staining for p-STAT3 antigen was performed in 74 surgically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 31 publications
3
33
0
Order By: Relevance
“…Reports of aberrant DNA methylation of SOCS genes in a number of breast cancer cell lines and tumors [29,30] have led to the suggestion that SOCS genes are silenced during oncogenic transformation of mammary tissue. In line with this supposition, decreased expression of SOCS3 has been positively correlated with increased metastatic potential in breast tumors [31]. On the other hand, constitutive expression of SOCS genes was reported in breast cancer lines [13] indicating absence of epigenetic transcriptional block.…”
supporting
confidence: 52%
“…Reports of aberrant DNA methylation of SOCS genes in a number of breast cancer cell lines and tumors [29,30] have led to the suggestion that SOCS genes are silenced during oncogenic transformation of mammary tissue. In line with this supposition, decreased expression of SOCS3 has been positively correlated with increased metastatic potential in breast tumors [31]. On the other hand, constitutive expression of SOCS genes was reported in breast cancer lines [13] indicating absence of epigenetic transcriptional block.…”
supporting
confidence: 52%
“…As an established negative regulator of STATs, SOCS3 function has been examined in vitro and in vivo using diverse transformed cell lines. It has been identified that forced expression of SOCS3 resulted in growth inhibition of human lung adenocarcinoma A549 cells (He et al 2003) and lung cancer xenografts in nude mice (Nakagawa et al 2008). Mice deficient in SOCS3 die in utero as a consequence of uncontrolled leukemia inhibitory factor (LIF) signaling inactivation of the LIF receptor rescues the SOCS3-/-phenotype (Takahashi et al 2008;Roberts et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Their data further revealed that deficient expression of SOCS3 was significantly associated with lymph node metastasis, blood vessel invasion, expression of VEGF and Ki-67 and reduced disease-free survival, concordant with our study in HCC. Moreover, Nakagawa et al (29) demonstrated that decreased expression of SOCS3 mRNA was correlated with tumor lymph node metastasis in breast carcinoma. However, Yang et al (21) detected the expression of SOCS3 in 87 HCC patients and observed that 67.8% of HCC lesions showed moderate to very strong SOCS3 staining, and increased expression of SOCS3 was positively associated with tumor vascular invasion and poor patient OS.…”
Section: Discussionmentioning
confidence: 99%